Pengembangan Model Pembelajaran Pendidikan Agama Islam Berbasis Teknologi dalam Era Digital di SMK Satria - Muhammad Fikri Hasan; Amin Fauzi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines the development of an Islamic religious education learning model based on technology at SMK Satria, in the era guided by Web 3.0. Semantic technology within Web 3.0 enables smarter interactions between humans and machines, with the potential to harness artificial intelligence (AI), Internet of Things (IoT), and blockchain technology. The primary objective of this research is to identify and develop an optimal learning model that integrates Islamic religious education with information technology within the SMK Satria environment. The research methodology employs a qualitative approach with a case study as the primary method. Data were collected through participatory observation, in-depth interviews with Islamic religious education teachers and students, and document analysis such as lesson plans. The data were analyzed using content analysis to identify patterns and themes related to the use of technology in Islamic religious education learning. The results indicate that the integration of information and communication technology (ICT) in Islamic religious education at SMK Satria has enhanced the effectiveness and interactivity of learning. The use of multimedia and ICT-based learning applications facilitates better understanding of Islamic concepts through interactive visualization and audio-visual content. Additionally, technology supports student-centered learning, allowing them to adjust their learning pace and enhancing their engagement in online discussions and collaborations.